Circadian Disruptions and Their Impact on Inflammatory Pathways, Neuroendocrine Dysregulation, and Cardiovascular Risk: A Systematic Review and Meta-Analysis - Rashid, Abdul; Mushtaq, Adil; Raghib, Shaheera; Shaik, Sumaiya Tarannum; Maloth, Arun Kumar; Khan, Aima Asim; Saad, Saja; Saad, Mohammed Saad; Alaleeli, Shamsa Bin Bader; Gafoor, Shasliya Abdul; Ali, Afrah Siraj Mujeeb (Indus Journal of Bioscience Research, 2025)
Background: Circadian disruptions, such as shift work, sleep irregularity, and chronic circadian misalignment, have been increasingly linked to adverse health outcomes, particularly affecting cardiovascular health. These disruptions alter inflammatory and neuroendocrine pathways, which may accelerate cardiovascular disease risk. This meta-analysis aimed to synthesize evidence on the association between circadian misalignment, inflammatory markers, neuroendocrine dysregulation, and cardiovascular outcomes. Methods: A systematic literature search was conducted using PubMed, Web of Science, PsycINFO, Cochrane Library, and Scopus databases, covering studies published between 2015 and 2024. Eligible studies included observational and experimental designs assessing the impact of documented circadian disruptions on inflammatory markers (CRP, IL-6, TNF-α), neuroendocrine biomarkers (cortisol, melatonin), and cardiovascular outcomes (coronary heart disease, cardiovascular events, metabolic risk). Quality assessment was performed using the Cochrane Risk of Bias Tool for experimental studies and the Newcastle-Ottawa Scale (NOS) for observational studies. Due to substantial heterogeneity across studies, a narrative synthesis supported by descriptive statistics, correlation analysis, and visual comparative techniques was applied, rather than a formal pooled effect size calculation. Results: Eight studies (n=744) reported increased inflammatory markers (CRP, IL-6, TNF-α) in circadian disruptions (p < 0.05–0.01). Misalignment was linked to altered cortisol rhythms and increased secretion (p < 0.05). Correlation analysis showed a moderate positive association between neuroendocrine dysregulation and cardiovascular risk. Shift work and chronic misalignment had the highest cardiovascular risk, with stronger effects in longer studies. Most studies had low-to-moderate bias. Conclusions: Circadian disruptions contribute to inflammation, neuroendocrine dysregulation, and cardiovascular risk. Maintaining circadian stability is crucial, particularly for shift workers. High-quality studies are needed for targeted interventions.